Rancang Bangun Alat Pendeteksi Warna Menggunakan Arduino Uno Berbasis IoT (Internet of Things) - Sri Wulandari; Budy Satria (Paradigma, 2021)
The rapid development of technology causes a series of electronic applications to replace the role of humans as accuracy and accuracy in a job. Based on observations in the industrial sector, there are still few who use the services of human hands to sort an object. Sorting by color is one of them. This IoT-based color detector is a simulation of a tool designed to help ease human work in sorting an object. Generally, color detection techniques are still manual, requiring the user to adjust from where the tool is located. Therefore, we need a tool that can detect colors that can be adjusted through IoT-based applications (Internet of Things) using the TCS3200 color sensor as a color detector, Arduino Uno as Data Processing and Microsoft Visual Basic .NET applications as the media interface. Supported by the HMI (Human Machine Interface) system as a system that regulates the process of running a job, and a Servo Motor as a rotary actuator (motor) in directing a running object, color detection will be more accurate and efficient. So that users can get or make it easier to detect the color according to the desired amount.